The other alliance : student protest in West Germany and the United States in the global sixties - Klimke, Martin, 1977- 1977- (America in the world, 2010)
SDS meets SDS -- Between Berkeley and Berlin, Frankfurt and San Francisco : the networks and nexus of transnational protest -- Building the second front : the transatlantic antiwar alliance -- Black and red panthers -- The other alliance and the transatlantic partnership -- Student protest and international relations